Targeted and untargeted metabolomics reveals deep analysis of drought stress responses in needles and roots of Pinus taeda seedlings - Wu, Chu; Wang, Yun; Sun, Honggang (Frontiers in Plant Science, 2023)
Drought stress is one of the major environmental stresses, affecting plant growth and yield. Although Pinus taeda are planted in rainy southern China, local drought sometime often occurs and last even couples of months. In this study, we carried out targeted and untargeted metabolomics analyses to evaluate drought tolerance of P. taeda. Targeted metabolomics analyses showed that levels of some sugars, phytohormones, and amino acids significantly increased in the roots and needles of water-stressed P. taeda seedlings, compared with well-watered pine seedlings, such as sucrose in pine roots, the two phytohormones abscisic acid and sacylic acid in pine needles, the phytohormone GA4 in roots, the two amino acids Gln and Asn in pine roots. Compared with well-watered pine seedlings, the neurotransmitter acetylcholine significantly increased in needles of water-stressed pine seedlings, but significantly reduced in their roots. L-glutamine and hydroxytyramine significantly increased in roots and needles of water-stressed pine seedlings, respectively, compared with well-watered pine seedlings, but noradrenaline significantly reduced in needles of water-stressed pine seedlings. Levels of some unsaturated fatty acids significantly reduced in roots or needles of WS pine seedlings, compared with well-watered pine seedlings, such as linoleic acid, oleic acid, myristelaidic acid, myristoleic acid in roots, and palmitelaidic acid, erucic acid, and alpha-linolenic acid in needles, however, three saturated fatty acids significantly increased in water-stressed pine seedlings, such as dodecanoic acid in pine needles, tricosanoic acid and heptadecanoic acid in pine roots. Untargeted metabolomics analysis showed that levels of some metabolites increased in water-stressed pine seedlings, especially sugars, long-chain lipids, flavonoids, and terpenoids. Few specific metabolites increased greatly, such as androsin, piceatanol, panaxatriol in roots and needles of water-stressed pine seedlings. Comparing well-watered and water-stressed pine seedlings, the most enriched pathways in pine needles included flavone and flavonol biosynthesis, ABC transporters, diterpenoid biosynthesis, plant hormone signal transduction, flavonoid biosynthesis; in pine roots, the most enriched pathways included tryptophan metabolism, caffeine metabolism, sesquiterpenoid and triterpenoid biosynthesis, plant hormone signal transduction, biosynthesis of phenylalanine, tyrosine and tryptophan. Under long-term drought stress, P. taeda seedlings showed their own metabolomics characteristics, providing a guideline for breeding drought-tolerant cultivars of P. taeda.